Negative emotional status and influencing factors among young employees in center of disease control and prevention - Lu Han; Qiyu Li; Yu Zhang; Tuo Liu; Ran Niu; Qi Wang; Lina Zhao (BMC Public Health, 2022)
Abstract Background Negative emotions among employees have become a public problem that increase the risk of developing the disease and accelerate its progression. This study aimed to investigate the status and influencing factors of negative emotions among young employees in center of disease control and prevention. Methods Participants included 6099 employees aged 40 or below in center of disease control and prevention (CDC) of 32 province of China were interviewed by online questionnaire survey. The emotional conditions of anxiety and depression, and their influencing factors were analyzed. Results A total of 5353 valid questionnaires were collected with the recovery rate of 87.77%. 2871 cases of young employees had different degrees of negative emotions at work, accounting for about 53.60%. Regression analysis showed that gender, professional title, educational level, job satisfaction, chronic diseases, daily sleep duration, average weekly overtime, physical activity time, and sugary beverage intake were the influencing factors of negative emotions (P < 0.05). Male, primary and below, never working overtime and daily physical activity time more than 30 min were protective factors for negative emotions (OR vale were 0.79, 0.68, 0.39 and 0.63, respectively, P < 0.05). Bachelor degree or above, poor job satisfaction, chronic disease, daily sleep duration less than 8 h and drinking one to three sugary drinks a week were the risk factors for negative emotion (OR vale were1.21, 4.32, 2.16, 2.75 and 1.20, respectively, P < 0.05). Conclusion Due to the influence of work pressure, lifestyle, chronic diseases and other factors, young employees in CDC have a certain degree of negative emotions at work, which should be paid enough attention. Meanwhile, corresponding measures should be taken according to the influencing factors to reduce the occurrence of negative emotions.